MANAJEMEN PENERAPAN ETIKA BELAJAR PESERTA DIDIK UNTUK MEMPEROLEH KESALEHAN AKADEMIK - ajangrifai (ASWAJA: Jurnal Pendidikan dan Keislaman, 2021)
ABSTRACT The title of this research is "Management of the Application of Learning Ethics for Students to Obtain Academic Virtue" This research was carried out in Madrasah Tsanawiyah Al-Kareem and Madrasah Tsanawiyah Al-Musthofa, Garut Regency. This writing arises from the fact that many of the students lack ethics in studying, causing a decline in ethical values, thin solidarity, increasing juvenile delinquency, various cases of declining morals of students today, especially at the high school level, and students have not yet received the fruits. knowledge and the blessing of science for not being able to understand the procedures for obtaining useful knowledge. The problems in this study are: How is the management of the application of students' learning ethics to obtain academic piety at Madrasah Tsanawiyah, Garut Regency. The purpose of this study was to obtain an overview of the planning, implementation, evaluation, supporting factors and obstacles faced in the management of the application of students' learning ethics to obtain academic piety. This study used a qualitative approach and data collection techniques were carried out through triangulation of observations, interviews and documentation studies, while the data sources were through triangulation: Head of Madrasah, Teachers and Students. The results of the study show: First, in the aspect of learning planning at Madrasah Tsanawiyah, Garut Regency, the teacher prepares an annual program, semester program, syllabus development and preparation of learning implementation plans. Second, in the aspect of learning implementation using the syllabus and lesson plans that were compiled by each teacher. The lesson plan is prepared by the teacher according to the time allocation. Third, in the aspect of learning evaluation, Madrasah Tsanawiyah Garut Regency carried out four stages, namely: 1) Initial evaluation to make a learning plan by analyzing the internal and external environment of the madrasa, 2) Evaluation of the process or implementation of learning. 3) Evaluation of learning outcomes to see how far the learning objectives have been achieved, 4) Evaluation of the overall learning program, this evaluation is carried out by madrasas at least once a month, six months and a year. Key words: Management, Learning Ethics, Students, Academic Piety